In Churchill's Footsteps: How Blair Bombed Out - Dobbs, Michael (Tufts Archival Research Center, 2005)
Volume 28, Issue 2. Summer Michael Dobbs compares the political leadership styles of four of Britain's most notable prime ministers: Clement Attlee, Margaret Thatcher, Tony Blair, and Winston Churchill.